2021
DOI: 10.3389/fgene.2021.608629
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Key Genes of Non-obstructive Azoospermia Affect Spermatogenesis: Transcriptomic Analysis Based on RNA-Seq and scRNA-Seq Data

Abstract: Non-obstructive azoospermia (NOA) is one of the most important causes of male infertility. It is mainly characterized by the absence of sperm in semen repeatedly or the number of sperm is small and not fully developed. At present, its pathogenesis remains largely unknown. The goal of this study is to identify hub genes that might affect biomarkers related to spermatogenesis. Using the clinically significant transcriptome and single-cell sequencing data sets on the Gene Expression Omnibus (GEO) database, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…As shown on Figure 1 D, the expression of all the 50 genes identified was dramatically reduced in the LPM/ST hLECs group. Amongst them, several are known to encode proteins that regulate particularly important epithelial cell functions such as apoptosis ( ST18 , CISD3 ) [ 39 , 40 ], differentiation ( TBR1 , BARX1 , NKX1-2 , FOXB1 , APOL1 , PROP1 , TSACC ) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], proliferation ( CEBPD , MNX1-AS1 , GPR75 , FZD9 , GAS2L3 , PFKL , TPT1-AS1 , CYP17A1 , MIR22HG ) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], and migration ( ARHGAP9 , ITGAM , EMILIN1 , ZNF554 , SOX8 ) [ 59 , 60 , 61 , 62 , 63 ]. Moreover, the involvement of some of these genes in the cellular functions listed above was validated further by our IPA analyses.…”
Section: Resultsmentioning
confidence: 99%
“…As shown on Figure 1 D, the expression of all the 50 genes identified was dramatically reduced in the LPM/ST hLECs group. Amongst them, several are known to encode proteins that regulate particularly important epithelial cell functions such as apoptosis ( ST18 , CISD3 ) [ 39 , 40 ], differentiation ( TBR1 , BARX1 , NKX1-2 , FOXB1 , APOL1 , PROP1 , TSACC ) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], proliferation ( CEBPD , MNX1-AS1 , GPR75 , FZD9 , GAS2L3 , PFKL , TPT1-AS1 , CYP17A1 , MIR22HG ) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], and migration ( ARHGAP9 , ITGAM , EMILIN1 , ZNF554 , SOX8 ) [ 59 , 60 , 61 , 62 , 63 ]. Moreover, the involvement of some of these genes in the cellular functions listed above was validated further by our IPA analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Klinefelter syndrome is an important cause of non‐obstructive azoospermia (NOA) and oligospermia, which is accompanied by impaired spermatogenesis, with 90% of patients presenting with azoospermia and 10% with severe oligospermia [ 19 , 20 ]. Furthermore, the effects of KS mosaicism may not be limited to germ cells;Ivan scholars [ 21 ] had found that KSM may be a factor in the pathogenic cascade in psychiatric and neurodegenerative disorders, particularly in cases where two or more X chromosomes are overrepresented.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, from the perspective of pathogenesis, although many theories have been proposed to explain the pathogenesis of NOA, our understandings of the biological processes associated with NOA remains insufficient. Nowadays, the widespread applications of gene sequencing, especially scRNA-seq, have deepened the knowledge of NOA [ 25 , 26 ]. For instance, Wang et al had disclosed the unique role of autophagy homeostasis in the spermatogenesis of NOA cases through scRNA-seq analysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%